The Development of Analytic Team Collaborative Learning Model Based on Brain-Based Learning (BBL) for Junior High School Science Learning in Agroecosystem Areas - Yolanda Leony Agustia Mertha; Imam Mudakir; Jekti Prihatin (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Abstract Students in the agroecosystem area are generally less active because the teacher does not utilize the potential of the surrounding agroecosystem. This can be overcome by applying Brain-Based Learning (BBL) approach combined with AT collaborative learning model. This study aimed to produce Analytic Team learning model based on Brain-Based Leaning (AT-BBL) that is valid, practical, and effective, and also improves the students' critical thinking skills and learning outcomes. This study used R&D with 4D development model which only carried out three stages, namely define, design, and development without using the disseminate stage. The average validation is 86.98 (highly valid). The average percentage of teacher responses is 92.94%, and the average percentage of student responses is 91.22% which is very practical. Keywords: Agroecosystem, BBL approach, Analytic Team Learning Model, Collaborative Learning